Transcription of the Tumor Suppressor Genes p53 and RB in Lymphocytes from Patients with Chronic Kidney Disease: Evidence of Molecular Senescence? - Kordinas, Vasileios (Hindawi Publishing Corporation, 2012)
Patients suffering from renal failure exhibit an impaired immune system function. We wanted to investigate the transcription of the tumor suppressor genes p53 and RB to record, if these cells could be stimulated in vitro in order to divide, after the addition of antigenic and inflammatory factors. This expression was measured by real-time PCR in peripheral blood mononuclear cells (PBMCs) from three different groups: ten healthy individuals, ten patients with chronic kidney disease (CKD), and ten dialysis patients with end stage renal disease (ESRD). The transcription rate of these genes was also measured after the cultivation of PBMCs under four different conditions: just with the culture medium, with lipopolysaccharide (LPS), with C-reactive protein (CRP), and with lipoxin A(4) (LXA(4))-LPS. Our results show that in most cases after the cultivation with additives, the transcription levels were higher in dialysis patients compared to those of the other two groups. Our findings serve as indications of cellular senescence on a molecular level, while it seems that these cells are less easily stimulated in vitro in order to duplicate.